New directions for tackling food safety risks in the informal sector of developing countries - Henson, S.; Jaffee, S.; Wang, S. (International Livestock Research Institute, 2023)
Informal food markets are important sources of affordable, nutritious food for millions of people in low- and middle-income countries. However, a large part of the public health burden of foodborne disease is associated with foods that are handled and sold by informal food processors and vendors.